EFEK PAPARAN RADIASI PENGION TERHADAP JUMLAH LEUKOSIT PEKERJA DI INSTALASI RADIOLOGI RUMAH SAKIT DI KUPANG, NTT - Selly, Jannes Bastian; Roga, Anderias Umbu; Berek, Noorce Christiani (RSUP Dr. Kariadi, 2022)
ABSTRACT BACKGROUND : Workers in hospital radiology installations are at risk of being exposed to ionizing radiation during work. Ionizing radiation has the potential to cause ionization in the body, so it can cause harm to workers. One of the efforts to minimize the risk of radiation exposure is to conduct regular health checks. OBJECTIVE: This study aims to identify the effects of radiation exposure, especially ionizing radiation received during work on the number of leukocytes of workers METHOD : The type of this research is observational analytic with cross sectional approach. Respondents in this study were 20 workers at radiology installations in 3 hospitals in Kupang who met the inclusion criteria specified. The independent variable (X) in this study is the dose of radiation exposure in units of milisieverts (mSv), while the dependent variable (Y) is the number of workers' blood leukocytes.. RESULT : The results showed that there was a significant effect of radiation exposure on the number of leukocytes of workers in radiology installations according to the equation Y = 3.959-3.989X with p-value 0.001 and R2 = 0.455 CONCLUSION : Exposure to ionizing radiation received by workers has an impact of 45.5% on a decrease in the number of leukocytes by 0.03 , every 1 unit dose increase Keywords: Radiation exposure doses, radiology installations, leukocytes, radiation workers, ionizing radiation